ASUHAN KEBIDANAN PADA IBU HAMIL HYPEREMESIS DENGAN PEMBERIAN OIL ESSENSIAL LEMON UNTU MENGURANGI MUNTAH DI WILAYAH PUSKESMAS BALIBO - Erniawati; Kurniati Akhfar; Erniawati M.; Nur Baeti (Akademi Kebidanan Tahirah Al Baeti Bulukumba, 2019)
Pregnancy is a natural process for a woman. The changes that occur in women during normal pregnancy are physiological, not pathological. The purpose of this study was to provide midwifery care to pregnant women by giving Lemon Essential Oil who experienced vomiting in the Balibo Health Center area. The research method used is by carrying out midwifery care in accordance with good and correct procedures, including encouraging pregnant women to inhale lemon essential oil by dripping 5 drops of lemon aromatherapy on a tissue. After doing midwifery care for 4 visits to patients for 4 days. then the results obtained on the first visit at BPM Azzahra Bantaeng with a frequency of nausea and vomiting 5 times in 24 hours. While the next visit was carried out at the patient's home with no more vomiting but with a different frequency of nausea but each visit the frequency of nausea had decreased.